Attitudes towards physical education lessons in students at different levels of education - Papla, Monika; Wojdała, Grzegorz; Rasek, Joanna; Królikowska, Paulina; Starzak, Joanna; Górna-Łukasik, Krystyna (Journal of Education, Health and Sport, 2019)
School physical education consists in interactions between teachers and students. It is important that each of those present in the classroom feel satisfied with their own results, but also with the way in which the required contents are taught. The aim of the study was to determine the attitudes of students towards physical education classes at different levels of education. The survey was conducted in September 2016 in a group of 157 students from the sixth grade of a primary school, third grade of a junior high school, and from a high school. The results of the survey were analysed separately for each level of education and each sex, and then girls and boys were compared between age groups. Schools from Bielsko-Biała which have similar conditions in terms of equipment and place of teaching classes were selected for the survey. The survey questionnaire by S. Strzyżewski and K. Górna (1989) was used in the study. The results showed that many elements of the lesson remain to discourage the student from practising. Insignificant differences were found depending on the level of education. The youngest girls and boys at every level of education like attending classes, but this tendency is not observed in the oldest girls.